Healthspan and chronic disease burden among young adult and middle-aged male former American-style professional football players. (7th December 2022) - Grashow, Rachel; Shaffer-Pancyzk, Taylor Valencia; Dairi, Inana; Lee, Hang; Marengi, Dean; Baker, Jillian; Weisskopf, Marc G; Speizer, Frank E; Whittington, Alicia J; Taylor, Herman A; Keating, Dylan; Tenforde, Adam; et al.
Abstract : Objective: To examine the relationships between age, healthspan and chronic illness among former professional American-style football (ASF) players. Methods: We compared age-specific race-standardised and body mass index-standardised prevalence ratios of arthritis, dementia/Alzheimer's disease, hypertension and diabetes among early adult and middle-aged (range 25–59 years) male former professional ASF players (n=2864) with a comparator cohort from the National Health and Nutrition Examination Survey and National Health Interview Survey, two representative samples of the US general population. Age was stratified into 25–29, 30–39, 40–49 and 50–59 years. Results: Arthritis and dementia/Alzheimer's disease were more prevalent among ASF players across all study age ranges (all p<0.001). In contrast, hypertension and diabetes were more prevalent among ASF players in the youngest age stratum only (p<0.001 and p<0.01, respectively). ASF players were less likely to demonstrate intact healthspan (ie, absence of chronic disease) than the general population across all age ranges. Conclusion: These data suggest the emergence of a maladaptive early ageing phenotype among former professional ASF players characterised by premature burden of chronic disease and reduced healthspan. Additional study is needed to investigate these findings and their impact on morbidity and mortality in former ASF players and other athlete groups.